Second Five Year Plan 1956-61 Himachal Pradesh - Planning Commission (Planning Commission, 1956)
The State is almost all mountainous with variable seasonal and climatic conditions. There are, at present, 31 Hospitals in the Status which are quite insufficient to cater for the Veterinary requirements. The existing hospitals are mainly situated in the Tehsil Headquarters. It is Very difficult to render veterinary aid in times of emergency when contagious outbreaks otc, occur in the interior of the illaqa where the majority of the Livestock population is maintained by the villagers. Those areas are situated in far off and remote corners and arc not accessible by modern moans of communication. The means of transportation in these areas are by Mules, Ponies, Donkeys, Sheep, Goats etc.
Animal Husbandry Department Government of Himachal Pradesh